PENGOPTIMALAN MANAJEMEN PEMBIAYAAN DAN ANGGARAN UNTUK EFEKTIVITAS PENGELOLAAN SARANA PRA SARANA PADA SEKOLAH MENENGAH PERTAMA - Widiastuti, Anik; Rokhim, Hanif Nur; Fahira, Sausan Azzah; Agata, Jovita Wahyu (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2023)
One of the key factors that influences the quality of education is financing and budget management, especially in the context of managing school infrastructure. This research aims to optimize financing and budget management in order to increase the effectiveness of school infrastructure management. The method used is a qualitative descriptive approach through library research or literature review using journals appropriate to the research topic with the aim of producing output based on available data and providing an explanation of the findings which can be used as a reference for further research studies. The research results show that optimizing financing and budget management can increase the effectiveness of infrastructure management. Concrete steps such as increasing the allocation of funds for maintaining infrastructure, increasing the capacity of school administrators in budget planning, and implementing an effective monitoring system can make a positive contribution to improving the quality of learning.